Analisa Kinerja Sistem Distribusi Air Bersih Pada PDAM Di Kota Ternate - Ardiansyah, Ardiansyah; Juwono, Pitojo Tri; Ismoyo, M. Janu (Fakultas Teknik, Universitas Brawijaya, 2012)
Fresh water providing system at Keluarahan Jati and Kelurahan Tanah Tinggi Barat in Sub- District of South Ternate City is not able to run smoothly yet, it may be caused by not maximum water supply during 24 hours and not maximum to take debit from the main spring.This research is aimed to know network ability including debit, pressure, continuity waters and to analyze customer satisfaction level for service system of fresh water distribution network at PDAM of Ternate City. Total of fresh water need is 1459.50 liter/day, as total of sufficient fresh water need. The water losing percentage is 20%, water losing level in 2012 is 0.002 liter/second. Result of running by Epanet 2.0 program on 07.00 was obtained unfit pressure with criteria planning (10-60 mH20) is as 70.97 m, the speed is more than standard planning (0.6-2.5 m/second), that is 0.01-0.09 (m/second). The little debit at node 4, node 11, are 0.71 m3/second. Questionnaire result is 53.61% stated not satisfaction and 26.80% stated very unsatisfied.Keywords: Debit, quality, quantity, continuity, pressure.